Sirtuin 1 promotes autophagy and proliferation of endometrial cancer cells by reducing acetylation level of LC3. (2nd February 2021) - Huang, Shuai; Li, Ye; Sheng, Guihua; Meng, Qingwei; Hu, Qian; Gao, Xuexiao; Shang, Zhiyuan; Lv, Qiubo
Abstract: Endometrial cancer (EC) constitutes a common female genital tract tumor with a rising incidence rate. Sirtuin 1 (SIRT1) is a member of histone deacetylase, which extensively participates in the progression of aging, cell death, and tumorigenesis. This study explored the effect of SIRT1‐mediated LC3 acetylation on autophagy and proliferation of EC cells. SIRT1 expression in EC tissues and adjacent tissues, EC cell lines and normal human epithelial cells was detected. SIRT1 expression was elevated in EC cell lines and tissues. Knockdown of SIRT1 inhibited proliferation, migration, and invasion of EC cells. Then, EC cells were starved in serum‐free medium, and levels of autophagy‐related proteins were detected. Starvation induced autophagy of EC cells. The starvation‐treated EC cells showed an increased SIRT1 expression, a decreased LC3 acetylation level and an increased autophagy level. The proliferation and autophagy of EC cells under different treatments were evaluated. In EC cells transfected with overexpressing SIRT1, LC3 acetylation was inhibited and cell proliferation was promoted. Moreover, overexpressing SIRT1 facilitated growth and autophagy of transplanted tumors in nude mice. In conclusion, SIRT1 promoted autophagy and proliferation of EC cells by reducing acetylation level of LC3.